PATIENT CARE DELIVERY THROUGH INNOVATIVE NURSING MODELS - Halima Muhammad Ali Hakami, Nouf Mohammed Alshallali, Zahra Omr Ali, Muteb Marzouq Mater Alayt, Mubarak Mesfer Alorem, Abdullah Shallan Al Roman, Mona Inad Sayer Alanazi, Mohammad Ahmed Saeed Alghamdi, Musa Mubark Musa Alenzi.,,; Abdulrahman Abdullah Ali Alshehri, Naif Mohammed Alanazi, Eishah Ali Muhnashy, Rami Ibrahim Alalawiy, Faisal Musa Munawar Al-Anazi, Rajaa Obied Alanazi, (Chelonian Research Foundation, 2022)
Ensuring that healthcare services are delivered in a manner that acknowledges and fulfills the requirements of patients and caregivers is crucial for encouraging good care consequences and opinions about care quality. This is an important component of meeting the criteria for patient-centered care. Effective interaction among patients and healthcare personnel is essential for the delivery of patient care and recuperation. Therefore, patient-centered communication is essential for achieving the best possible health results. This approach aligns with longstanding nursing principles that emphasize the need for personalized treatment that addresses patient health issues, opinions, and contextual factors. Attaining patient-centered attention and interaction in nurse-patient clinical encounters is intricate due to the presence of several obstacles, including organizational, interaction, ecological, and personal/behavioral factors. In order to advance patient-centered care, healthcare practitioners need to recognize the obstacles and facilitators that affect both patient-centered care and interaction, considering their interconnectedness in clinical encounters. The PC4 Model is a suggested framework that aims to guide healthcare workers in understanding care methods, discourse settings, and communication contents and forms that may either improve or hinder the achievement of patient-centered care in the clinical setting. Keywords: Patient care, nursing staff, treatment, PC4 model, obstacles, interaction.